Physiological, epigenetic and genetic regulation in some olive cultivars under salt stress. - Mousavi, Soraya; Regni, Luca; Bocchini, Marika; Mariotti, Roberto; Cultrera, Nicoló M.; Mancuso, Stefano; Googlani, Jalaladdin; Chakerolhosseini, Mohammad R.; Guerrero-Ruiz, Consolación María; Albertini, Emidio; Baldoni, Luciana; Proietti, Primo (Springer Nature, 2019)
Cultivated olive, a typical fruit crop species of the semi-arid regions, could successfully face the new scenarios driven by the climate change through the selection of tolerant varieties to salt and drought stresses. In the present work, multidisciplinary approaches, including physiological, epigenetic and genetic studies, have been applied to clarify the salt tolerance mechanisms in olive. Four varieties (Koroneiki, Royal de Cazorla, Arbequina and Picual) and a related form (O. europaea subsp. cuspidata) were grown in a hydroponic system under different salt concentrations from zero to 200 mM. In order to verify the plant response under salt stress, photosynthesis, gas exchange and relative water content were measured at different time points, whereas chlorophyll and leaf concentration of Na+, K+ and Ca2+ ions, were quantified at 43 and 60 days after treatment, when stress symptoms became prominent. Methylation sensitive amplification polymorphism (MSAP) technique was used to assess the effects of salt stress on plant DNA methylation. Several fragments resulted differentially methylated among genotypes, treatments and time points. Real time quantitative PCR (RT-qPCR) analysis revealed significant expression changes related to plant response to salinity. Four genes (OePIP1.1, OePetD, OePI4Kg4 and OeXyla) were identified, as well as multiple retrotransposon elements usually targeted by methylation under stress conditions.
Keywords: Olivos - Genética; Plantas - Efectos de la sal; Plantas - Efectos del estrés; Gene expression; Epigenetics; Salt stress; Olive; Methylation; Physiological studies; Climate change